Circulating Proprotein Convertase Subtilisin/Kexin Type 9 Levels and Cardiometabolic Risk Factors: A Population-Based Cohort Study - Shi, Jie; Li, Xiaoyong; Zhang, Weiwei; Niu, Yixin; Lin, Ning; Zhang, Hongmei; Ning, Guang; Fan, Jiangao; Qin, Li; Su, Qing; Yang, Zhen (Frontiers in Cardiovascular Medicine, 2021)
Aims: To evaluate the prospective association of circulating PCSK9 levels with the cardiometabolic risk profiles (high LDL-cholesterol, high triglycerides, low HDL-cholesterol, hypertension, type 2 diabetes, and metabolic syndrome). Methods: A population-based prospective study was conducted among 7,104 Chinese individuals (age 56.2±7.5 years; 32.0% men). Circulating PCSK9 levels were measured using ELISA. Results: Circulating PCSK9 levels were higher in women than men (286.7 ± 90.1 versus 276.1 ± 86.4 ng/ml, p <0.001). And circulating PCSK9 was positively correlated with LDL-cholesterol, total cholesterol, and triglycerides both in men and women (all p <0.001). The positive correlation between PCSK9 and waist circumference, fasting glucose, insulin resistance, systolic blood pressure, diastolic blood pressure and C-reactive protein (all p <0.01) was observed in women only. According to Cox regression analysis, circulating PCSK9 was positively associated with incidence of high LDL-cholesterol both in men (HR 1.33, 95% CI 1.09-1.65, p <0.001) and women (HR 1.36, 95% CI 1.12-1.69, p <0.001). Moreover, PCSK9 was significantly associated with incident high triglycerides (HR 1.31, 95% CI 1.13-1.72, p <0.001), hypertension (HR 1.28, 95% CI 1.08-1.53, p =0.011), type 2 diabetes (HR 1.34, 95% CI 1.09-1.76, p =0.005), and metabolic syndrome (HR 1.30, 95% CI 1.11-1.65, p =0.009) per SD change in women only. No statistically significant association was observed between circulating PCSK9 and incidence of low HDL-cholesterol (p >0.1). Conclusions: Elevated circulating PCSK9 was significantly associated with cardiometabolic risk factors and independently contributed to the prediction of cardiometabolic risks in women.